A Myocardial Slice Culture Model Reveals Alpha-1A-Adrenergic Receptor Signaling in the Human Heart - R. Croft Thomas, Jr., MD; Abhishek Singh, MD, PhD; Patrick M. Cowley, PhD; Bat-Erdene Myagmar, MD, PhD; Megan D. Montgomery, PhD; Philip M. Swigart, BS; Teresa De Marco, MD; Anthony J. Baker, PhD; Paul C. Simpson, MD (JACC: Basic to Translational Science, 2016)
The authors used 52 nonfailing and failing human hearts to develop a simple, high throughput left ventricular myocardial slice model that is stable by ATP and viability assays for at least 3 days. The model supports studies of signaling, contraction, and viral transduction. They use the model to show for the first time that the alpha-1A-adrenergic receptor, which is present at very low abundance in the human myocardium, activates cardioprotective ERK with nanomolar EC50 in failing heart slices and stimulates a positive inotropic effect. This model should be useful for translational studies, to test whether molecules discovered in basic experiments are functional in the human heart.